Aisas Model Analysis on Food Business La Maison, Medan - Tasya Natalia Wijaya; Almayra Audrey Sundayana; Syifa Fadila; Ira Wirasari; Elsa Graciana Nugraeni (Syntax Corporation Indonesia, 2023)
La Maison is a dessert shop that focuses on French desserts such as macarons, cupcakes, croissants, cookies, cakes, etc. Opened in 2011, La Maison is very well known in Medan and many of its customers request it to be open in Indonesia capital city, Jakarta. Now La Maison has opened 5 branches, two in Medan and the other three in Jakarta, Indonesia. This research is intended to analyze La Maison with the AISAS model. AISAS is an acronym for Attention, Interest, Search, Action, and Share. AISAS is used as stages or steps in promotion from the moment it captures the consumer's attention to sharing the product/service to others. The information and data is compiled by using a descriptive qualitative method that analyzes data and information and interprets it in detail. This research shows that La Maison follows AISAS steps and succeeded until the last step where buyers share positive things about La Maison desserts.